Violência entre namorados na adolescência: Violence between partners in adolescence - R. Taquette, Stella (Adolescência e Saúde, 2009)
The violence between partners in adolescence is an almost invisible phenomenon and rarely identified in health services, that can have serious and sometimes fatal outcomes. Like the adolescent Eloá, that was victim of her boyfriend a few months ago, in the city of Santo André. Such violence results from the power that is attributed to men by the patriarchal society, in which men are considered owners of women. It is not different of the violence that victims elder women, but is more wicked in teenagers, that are more vulnerable and have fewer protection mechanisms. The purpose of this article is to make health professionals aware about this matter and to contribute for the precocious detection of violence and its confrontation.